2015
DOI: 10.21608/jppp.2015.74712
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Persistence of Spinetoram Against Three Stored Product Insect Pests

Abstract: The efficacy and the residual toxicity of spinetoram insecticide were evaluated in the laboratory at 26 ± 2°C and 60 ± 5RH against the adults of three insect species of stored products i.e., the rice weevil Sitophilus oryzae (L.), the lesser grain borer Rhizopertha dominica (F.) and the red flour beetle Tribolium castaneum (Herbst.). The obtained results showed that, the toxicity of spinetoram to the adults of the three insect species was concentration and exposure period -dependent.The susceptibility of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Results indicated that, the adults of R. dominica were highly susceptible to spinetoram than the two tested insects. The obtained results are in harmony with the findings of other investigators At hanassiou andKavallieratos, 2014 andNasr, 2015).…”
Section: Effect Of Spinetoramsupporting
confidence: 92%
“…Results indicated that, the adults of R. dominica were highly susceptible to spinetoram than the two tested insects. The obtained results are in harmony with the findings of other investigators At hanassiou andKavallieratos, 2014 andNasr, 2015).…”
Section: Effect Of Spinetoramsupporting
confidence: 92%